2015
DOI: 10.1002/sce.21181
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Teacher Intervention in the Intersection of Digital Resources, Peer Collaboration, and Instructional Design

Abstract: This paper reports on a case study of the teacher's role as facilitator in computer‐supported collaborative learning (CSCL) settings in science. In naturalistic classroom settings, the teacher most often acts as an important resource and provides various forms of guidance during students’ learning activities. Few studies, however, have focused on the role of teacher intervention in CSCL settings. By analyzing the interactions between secondary school students and their teacher during a science project, the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 44 publications
4
32
0
2
Order By: Relevance
“…However, research on students' learning in lab-work settings, including computer-supported lab settings, have shown that linking the practical lab work to a conceptual understanding of the underlying scientific principles and procedures is challenging for students (van Joolingen et al 2007;Lunetta et al 2007;Renken and Nunez 2013). Studies focusing on teacher support in computer-supported settings have shown that such support is pivotal (Gillen et al 2008;Strømme and Furberg 2015). The empirical findings of the current study are in line with and supplement findings from previous research showing that students struggle to link their experiences with practical lab work to an understanding of scientific principles, concepts and procedures.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, research on students' learning in lab-work settings, including computer-supported lab settings, have shown that linking the practical lab work to a conceptual understanding of the underlying scientific principles and procedures is challenging for students (van Joolingen et al 2007;Lunetta et al 2007;Renken and Nunez 2013). Studies focusing on teacher support in computer-supported settings have shown that such support is pivotal (Gillen et al 2008;Strømme and Furberg 2015). The empirical findings of the current study are in line with and supplement findings from previous research showing that students struggle to link their experiences with practical lab work to an understanding of scientific principles, concepts and procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have focused on the role of student-teacher interactions during inquiry-related group work in CSCL settings (Jornet and Roth 2015;Strømme and Furberg 2015). For instance, analyses of student-teacher interactions in an inquiry project about heat loss and emission of modern houses showed that the teacher-student interactions became important resources for the students to understand and take advantage of co-existing support features made available to them within the instructional setting.…”
Section: Teacher Support In Computer-supported Learning Settingsmentioning
confidence: 99%
See 3 more Smart Citations